Hamamelis virginiana L. Leaf Extracts Inhibit Some Bacterial Triggers of Selected Autoimmune Inflammatory Diseases - Nguyen, Cindy; Cock, Ian Edwin (Pharmacognosy Communications)
Background: Hamamelis virginiana L. leaves were used traditionally to treat bacterial infections and inflammation. Despite the traditional uses, relatively few studies have examined the ability of H. virginiana leaf extracts to inhibit the growth of the bacterial triggers of autoimmune inflammatory diseases. Materials and Methods: Hamamelis virginiana extracts were screened for growth inhibitory activity against bacterial triggers of multiple sclerosis (MS) and rheumatic fever (RF) by disc diffusion assays and the potency was quantified using liquid dilution MIC assays. Toxicity was evaluated using the Artemia nauplii cytotoxicity assay (ALA) and the therapeuitic index was calculated as a measure of therapeutic safety. Results: Hamamelis virginiana extracts strongly inhibited the growth of some bacterial triggers of MS and RF. The methanolic extract was a particularly good inhibitor of an antibiotic-resistant strain of P. aeruginosa (MIC=113 μg/mL), although it also had noteworthy inhibitory activity against A. baylyi and S. pyogenes (245 and 368 μg/mL respectively). The aqueous H. virginiana leaf extract also displayed noteworthy activity against the same bacteria, albeit with higher MIC values (560-1120 μg/mL). Both extracts have potential for preventing the onset of MS and RF, and for treating these diseases and decreasing the symptoms once they have been initiated. Additionally, the methanolic and aqueous extracts potentiated the activity of several conventional antibiotics in bacterial strains otherwise resistant to those antibiotics. Notably, both the methanolic and aqueous extracts synergised the activity of tetracycline against all bacteria tested, indicating that combinations containing tetracycline may be particularly useful in preventing MS and RF. None of the H. virginiana leaf extracts were toxic in the ALA toxicity assay. Conclusion: Hamamelis virginiana leaf extracts inhibit the growth of some bacterial triggers of MS and RF, as well as potentiating the activity of conventional antibiotics. Further in vivo studies to determine the anti-inflammatory and antibacterial mechanisms are warranted.
Keywords: Witch-hazel; North American plants; Antibacterial activity; Skin therapy; Inflammation; Multiple sclerosis; Rheumatic fever; Tannins.